Pro-carcinogenic actions of miR-155/FOXO3a in colorectal cancer development: miR-155/FOXO3a in colorectal cancer - Wang, Dianxiu; Geng, Wei; Han, Lu; Song, Ran; Qu, Qiusi; Chen, Xingyuan; Luo, Xi (Cellular and Molecular Biology, 2023)
Colorectal cancer (CRC) ranks third in cancer incidence and second in cancer mortality globally. MicroRNAs (miRNAs) are promising biomarkers and therapeutic targets for CRC diagnosis and treatment. The miR-155 is reported to induce radiation resistance in CRC. In this study, we aimed to further clarify the role and underlying mechanism of the miR-155 in CRC cell malignancy. We found that miR-155 was significantly up-regulated in CRC tissues. The results of loss-of-function experiments revealed that miR-155 deficiency suppressed the proliferative capacity, invasion, and migration of CRC cells. Moreover, the downstream target genes of miR-155 were screened, and miR-155 was demonstrated to directly bind to FOXO3a in CRC cells to negatively regulate FOXO3a expression. FOXO3a was downregulated in CRC tissues and the expression of FOXO3a and miR-155 was in negative correlation in CRC tissues. FOXO3a overexpression alone was revealed to inhibit CRC cell growth, migration and invasion. Additionally, rescue assays showed that FOXO3a silencing significantly reversed the inhibitory effect of miR-155 deficiency on CRC cell malignant behaviors. In conclusion, miR-155 induces malignant phenotypes of CRC cells including cell proliferation, migration and invasion by targeting FOXO3a, which might provide clues for the targeted therapy of CRC.